Who cares about financialization? Explaining the decline in political salience of active markets for corporate control - Helen Callaghan (Max Planck Institute for the Study of Societies, 2013)
Why is unprecedented financialization failing to provoke a strong political backlash? The role of financial markets, motives, actors, and institutions has expanded continuously in recent decades, but - contrary to Polanyi's 'double movement' theory and despite the current financial crisis - market-containment efforts have grown weaker over time. The present paper approaches this puzzle by explaining how the practice of corporate takeover bids gradually gained political acceptance in the United Kingdom from the 1950s onward. Through its expansion, the market for corporate control contributed directly to eroding political resistance by triggering processes of routinization, adaptation, and elimination. Routinization decreases issue salience for 'average voters' because it lowers the news value of takeover bids. Adaptation to new profit opportunities increases the number of beneficiaries from takeover bids, thereby bolstering promarket clienteles. Elimination of stakeholder-oriented companies - through constant exposure to takeover threats - demoralizes the opponents of active markets for corporate control by leaving them with less to fight for. Empirical evidence is drawn mainly from qualitative and quantitative analysis of British parliamentary debates regarding takeover bids between 1953 and 2011. – – Warum provoziert die historisch beispiellose Finanzialisierung keine starke politische Gegenreaktion? Während der Einfluss der Finanzwelt auf Märkte, Motive, Akteure und Institutionen im vergangenen Jahrzehnt kontinuierlich gewachsen ist, sind Bestrebungen zur Markteindämmung schwächer geworden - entgegen Polanyis Theorie der Doppelbewegung und trotz der gegenwärtigen Finanzkrise. Der vorliegende Aufsatz nähert sich diesem Rätsel, indem dargelegt wird, wie die Praxis von Übernahmeangeboten in Großbritannien seit den 1950er-Jahren allmählich an politischer Akzeptanz gewonnen hat. Durch seine Ausdehnung hat der Markt für Unternehmenskontrolle direkt zur Erosion politischen Widerstands beigetragen, indem er Prozesse der Routinisierung, Anpassung und Eliminierung ausgelöst hat. Routinisierung verringert die Bedeutung des Themas für den 'Durchschnittswähler', da sie den Nachrichtenwert von Übernahmeangeboten senkt. Anpassung an neue Profitmöglichkeiten erhöht die Zahl der Nutznießer von Übernahmeangeboten und stärkt so marktfreundliche Parteien. Eliminierung von stakeholderorientierten Unternehmen durch konstante Übernahmedrohungen demoralisiert die Gegner aktiver Märkte für Unternehmenskontrolle, da sich Widerstand weniger lohnt. Als empirische Belege werden quantitative und qualitative Analysen britischer Parlamentsdebatten zwischen 1953 und 2011 herangezogen.
Keywords: 300